Design And Analysis For A New Design Of Bending Arm On Bending Machine - ABDULLAH, SHERIL NADYA ROSARJUNA; Katimon, Mohd Nizam (Research Progress in Mechanical and Manufacturing Engineering, 2024)
This study presents the design produced for the bending arm component of the bending machine. This study was conducted for improvements so that the component is more durable and can withstand heavier loads. In the precast industry, bending machines are very important to form the material produced for development, which is the building's bones. Bending arm on this bending machine is an important component to shape the product produced. Therefore, this bending arm needs to be improved. With this improvement, the maintenance of the bending arm is less and thus can save costs for the precast industry. This study was carried out by giving the idea of some new designs for the bending arm and then choosing the most suitable bending arm material to maintain the durability of the bending arm. This study was conducted using analysis in Solidworks software. Data collection is done by comparing the maximum value for each material with the yield strength value. This data can be collected by placing a certain load value for each material. Based on this research, the tool stee l match with the suitability to be used on the bending arm, this is because the maximum value of von mises for each load applied to the bending arm is not close to the high yield strength of the tool steel.